Does Institutional Quality Shape the Laffer Curve? Evidence from Selected EU Economies - Draganić, Marina; Glavaški, Olgica; Pejčić, Jovica (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper examines whether institutional quality shapes the relationship between capital taxation and public revenues within the Laffer curve framework. Using tax revenues as a percentage of GDP as the dependent variable, and the Effective Average Tax Rate (EATR) on capital, government effectiveness, and rule of law as key determinants, the analysis explores how institutional capacity conditions fiscal performance. The sample comprises nine EU economies: Denmark, the Netherlands, Sweden, Estonia, Portugal, the Czech Republic, Greece, Bulgaria, and Romania, over the period 2004–2023. Employing the Pooled Mean Group (PMG) estimator, the results indicate a positive long-run effect of EATR on revenues and a negative coefficient on its squared term, confirming a non-linear Laffer-type relationship. Institutional indicators are positively and significantly associated with revenues, while the error correction term confirms stable long-run adjustment. Overall, stronger institutions shape the nonlinear revenue response, contributing to greater fiscal sustainability.